Classification criteria for cervical radiculopathy: An international e-Delphi study. (October 2022) - Lam, Kwun N.; Heneghan, Nicola R.; Mistry, Jai; Ojoawo, Adesola O.; Peolsson, Anneli; Verhagen, Arianne P.; Tampin, Brigitte; Thoomes, Erik; Jull, Gwendolen; Scholten -Peeters, Gwendolyne G.M.; Slater, Helen; Moloney, Niamh; et al.
Abstract: Background: Establishing a set of uniform classification criteria (CC) for cervical radiculopathy (CR) is required to aid future recruitment of homogenous populations to clinical trials. Objectives: To establish expert informed consensus on CC for CR. Design: A pre-defined four round e-Delphi study in accordance with the guidance on Conducting and Reporting Delphi Studies. Methods: Individuals with a background in physiotherapy who had authored two or more peer-reviewed publications on CR were invited to participate. The initial round asked opinions on CC for CR. Content analysis was performed on round one output and a list of discrete items were generated forming the round two survey. In rounds two to four, participants were asked to rate the level of importance of each item on a six-point Likert scale. Data were analysed descriptively using median, interquartile range and percentage agreement. Items reaching pre-defined consensus criteria were carried forward to the next round. Items remaining after the fourth round constituted expert consensus on CC for CR. Results: Twelve participants participated with one drop out. The final round identified one inclusion CC and 12 exclusion CC. The inclusion CC that remained achieved 82% agreement and was a cluster criterion consisting of radicular pain with arm pain worse than neck pain; paraesthesia or numbness and/or weakness and/or altered reflex; MRI confirmed nerve root compression compatible with clinical findings. Conclusions: The CC identified can be used to inform eligibility criteria for future CR trials although caution should be practiced as consensus on measurement tools requires further investigation. Highlights: An e-Delphi study was conducted to establish expert consensus on classification criteria (CC) for cervical radiculopathy (CR). One inclusion CC and twelve exclusion CC were identified. Identified CC can be used to inform eligibility criteria for future CR trials.